Phytochemical, GC-MS Analysis, and Antibacterial Activity of Ethanol Extract Coir and Shell U Groh (Cocos nucifera L.) - Misrahanum Misrahanum; Nurul Alfiyani; Hira Helwati; Sadli Sadli (Majalah Obat Tradisional, 2022)
U Groh is a coconut (Cocos nucifera L.) in which the meat has not been formed yet, and its shell is consumed as a salad by the Acehnese people. This study aims to determine the phytochemicals, GC-MS analysis, and activity of coir and shell U Groh against S. aureus and E. coli bacteria. Chemical compounds were analyzed using reagents and GC-MS. Antibacterial activity was tested using well diffusion with concentrations of 5, 10, 20, and 40%. Coir and shells contain flavonoids, tannins, and saponins. GC-MS analysis shows the coir contains 20 compounds, among others Alpha. - Bisabololoxide B-Acetate, Hexadecanoic acid, Hexadecanoic acid methyl ester, 9 octadecenoic acid methyl ester, Stigmasterol, and gamma. -Sitosterol, whereas 16 compounds for the shell Hexadecanoic acid, Hexadecanoic acid methyl ester, and Stigmast-5-en-3-ol. The highest activity of coir and shell U Groh against E. coli and S. aureus was a concentration of 40%. The antibacterial activity of U Groh coir and shell extract was more effective in inhibiting S. aureus than E. coli. Coir ethanol extract and its shell formed inhibition zones with diameters of 13.7 mm and 13.4 mm, respectively, against S. aureus, and the diameters against E. coli were 11.3 mm and 11.03 mm, respectively. The extract ethanol of coir and shell U Groh has good potential as an antibacterial.